SENTRALISASI PENDIDIKAN DAN DESENTRALISASI - Ghifari, Silfi; Nurdiana, Siti; Pazila, Ananda; Ananda, Rizki; Nasrul, Nasrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research investigates the centralization of education and decentralization. Using a literature review method, this research seeks to examine the correlation between scientific journals in the selected discourse. In the field of education management, there are two different regulatory frameworks: centralization and decentralization systems. In a centralized system, all aspects of education delivery are closely supervised by the central government. In contrast, in a decentralized system, regulatory power is delegated to local governments. In reality, these systems are often applied on a spectrum, with responsibilities and authority shared between central and local institutions. Decentralization of education will empower educational leaders to strategically foster and advance their respective regions, thereby promoting optimal growth and development.